Interview with Theo Rosier - Rosier, Theo; Rijn, van, Michela (Utrecht Journal of International and European Law, 2011)
On 21 January 2009, the Amsterdam Court of Appeal had ordered the Public Prosecution Service (OM) to subpoena Dutch politician Geert Wilders for, inter alia, spreading hatred and offending a group because of their religious convictions contrary to articles 137d and 137c of the Dutch Criminal Code. On Monday 24 May, the Amsterdam Court of First Instance rejected all preliminary objections formulated by Wilder's attorney Bram Moszkowicz. High time to scrutinise the precise merits of this prosecution and to re-examine an age old controversy: the perceived clash between the right to freedom of speech and (the right to freedom of) religion.